2003
DOI: 10.1152/ajplung.00220.2002
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil elastase increases MUC4 expression in normal human bronchial epithelial cells

Abstract: In chronic obstructive pulmonary diseases, the airway epithelium is chronically exposed to neutrophil elastase, an inflammatory protease. The cellular response to neutrophil elastase dictates the balance between epithelial injury and repair. Key regulators of epithelial migration and proliferation are the ErbB receptor tyrosine kinases, including the epidermal growth factor receptor. In this context, we investigated whether neutrophil elastase may regulate expression of MUC4, a membrane-tethered mucin that has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 47 publications
3
54
1
1
Order By: Relevance
“…We have recently reported that NE upregulates a cytoplasmic oxidoreductase, NADPH quinone oxidoreductase 1 that is required for NE-induced lipid peroxidation and for NE-regulated MUC5AC mRNA expression . NE also upregulates two membrane-associated mucins, MUC4 (Fischer, 2003) and MUC1 (Kuwahara et al, 2005), in airway epithelial cells. MUC1 and MUC4 regulate intracellular signaling via the ErbB family of receptor tyrosine kinases in cancer cells (Hollingsworth and Swanson, 2004) and may have similar functions in the lung.…”
Section: Neutrophil Elastase and Mucins Mucus Secretion And Mucocilmentioning
confidence: 98%
“…We have recently reported that NE upregulates a cytoplasmic oxidoreductase, NADPH quinone oxidoreductase 1 that is required for NE-induced lipid peroxidation and for NE-regulated MUC5AC mRNA expression . NE also upregulates two membrane-associated mucins, MUC4 (Fischer, 2003) and MUC1 (Kuwahara et al, 2005), in airway epithelial cells. MUC1 and MUC4 regulate intracellular signaling via the ErbB family of receptor tyrosine kinases in cancer cells (Hollingsworth and Swanson, 2004) and may have similar functions in the lung.…”
Section: Neutrophil Elastase and Mucins Mucus Secretion And Mucocilmentioning
confidence: 98%
“…Neutrophilic products such as proteases and oxidants have been evaluated for their role in regulating MUC gene expression. Neutrophil elastase, a serine protease, increases expression of at least two major respiratory tract mucin genes, MUC5AC (135,291) and MUC4 (77). Neutrophil elastase can regulate MUC5AC by at least two different mechanisms: 1) NE induces oxidant stress in A549 and NHBE cells (79) and regulates MUC5AC, as well as MUC4 by a posttranscriptional mechanism, e.g., by prolonging mRNA half-life, as briefly discussed in section IIID; and 2) NE releases TGF-␣ resulting in EGFR activation and transcriptional regulation of MUC5AC in H292 cells (135).…”
Section: Transcriptional Regulation By Inflammatory/ Immune Responmentioning
confidence: 99%
“…IL-4, IL-9, and NE have also been reported to increase expression of MUC4 in airway epithelial cells. In the case of the IL-4 and IL-9, transcriptional activation was believed to be the mechanism (131,132), whereas for NE increase in mRNA stability occurred (133).…”
Section: Regulation Of Other Mucin Genes In the Lungsmentioning
confidence: 99%